Aristotle’s Metaphysics of Matter - Massie, Pascal (Peitho. Examina Antiqua, 2025)
The issue of prime matter divides Aristotle’s modern commentators on two questions: a) whether Aristotle was truly committed to it b) whether the notion is even coherent. Those who declare prime matter incoherent do so on the ground that what is deprived of characteristics or properties is simply nothing. Those who try to salvage the notion claim that it must have some characteristics focus on extension. As it stands, the debate turns on the possibility or impossibility of reifying prime matter. If we can, then it can be a coherent ontological category; if we cannot, then it is incoherent. This paper proposes a different path: indeed, prōtē hulē cannot be reified, but this does not make it incoherent. This, however, invites us to pursue ontology beyond substantialism and essentialism and takes us to the limits of Aristotelianism.